2014
DOI: 10.5665/sleep.4248
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Home Single-Channel Nasal Pressure for Sleep Apnea Diagnosis

Abstract: Clinicaltrials.gov identifier: NCT01347398.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 30 publications
2
13
1
4
Order By: Relevance
“…Overall, we had a relatively low participation rate (70% of all patients recruited) of patients who spent one night with the ApneaLink TM at home and one night in the sleep laboratory for PSG examination. However, another study reported 79% of valid ApneaLink TM autoscore recordings [ 37 ], which is comparable with our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, we had a relatively low participation rate (70% of all patients recruited) of patients who spent one night with the ApneaLink TM at home and one night in the sleep laboratory for PSG examination. However, another study reported 79% of valid ApneaLink TM autoscore recordings [ 37 ], which is comparable with our study.…”
Section: Discussionsupporting
confidence: 92%
“…We also recommend that issues such as marital problems, loss of job, or experiencing a traffic accident are not disregarded, as these problems may occur simultaneously and might be complications of an OSAS [ 50 ]. The use of the automatic ApneaLink TM device requires development of integrated networks between nonspecialist and specialist practitioners to allow achieving an expert system to be managed by nonexperts [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 21 Our results show that RDI MAN agreed slightly better than RDI RAW with the laboratory AHI but, again, the differences were small compared with the confidence limits. Our Bland-Altman plots did not show the large differences between the manually scored and the computer-scored RDI for the ApneaLink Plus that were reported in a recent paper by Aurora et al 22 Unlike the 2014 paper from Masa et al , 23 we did not see much difference between the receiver–operator characteristic curves for mild, moderate and severe sleep apnoea when comparing the laboratory polysomnography with home testing performed on a different night. However, they had studied a much larger group of participants than we did and they used the ApneaLink, which records only nasal airflow, rather than the four-channel ApneaLink Plus.…”
Section: Discussioncontrasting
confidence: 84%
“…Portable sleep monitors (PMs), which can also be used in the home environment, are being used more frequently because of their simplicity, costs, and effectiveness. [8,9] In this study, we aimed to investigate the diagnostic efficacy of PMs in Turkish population by comparing them with the parameters of PSG, the apnea-hypopnea index (AHI), and the oxygen desaturation index (ODI) in the laboratory.…”
Section: Introductionmentioning
confidence: 99%